IFRS 9- Impacto Sector Bancário - Castro, Silvia Filipa Escovar de (2022)
The implementation of International Financial Reporting Standard 9 (IFRS 9) has been shown to be the major transformation in financial institutions accounting since international accounting standards were applied in 2015. IFRS 9 comes into force in January 2018, replacing IAS39, causing significant changes in the accounting of financial instruments. The incurred loss model used until now with IAS 39, is replaced by the expected loss model established by IFRS9. This dissertation analyzes the impacts in Banking Sector, with the implementation of this standard - IFRS 9- Impact on the Banking Sector. Regarding the methodology, this will be the collection of management reports/annual accounting documents between 2015 and 2020 of the Banks and afterwards, the treatment of the acquired information, considering it as a methodology of quantitative nature. The outcome of the tests supported by the Income Statements and Balance Sheets in IAS 39 and IFRS 9 in nine National and Foreign Banks, between 2015 and 2020, confirmed the research hypotheses which indicated that: levels of impairment recorded in the financial statements in IFRS 9 were higher than those recorded in the statements in IAS 39 and there is a higher result in the recording of impairments in credit operations (Loans to individuals and Loans to Companies) when compared with credit operations recorded on the basis of IAS 39. Thereby, the theoretical principles are confirmed that the expected loss model originates an increase in the recording of impairments compared to the incurred loss model.